COMPARISON OF TRADITIONAL AND NOVEL HEMOSTATIC PARAMETERS IN CHILDREN WITH ITP - To’ymurodova Zarinabonu Elmurod qizi, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This study evaluates the comparative utility of traditional versus novel hemostatic parameters in children diagnosed with idiopathic thrombocytopenic purpura (ITP). While platelet counts and standard coagulation tests remain the primary diagnostic tools, emerging markers such as platelet activation assays, thromboelastography, and endothelial function indicators provide additional insights into bleeding risk and disease severity. The study highlights differences in predictive value between conventional and advanced markers, emphasizing the importance of integrating novel hemostatic assessments for comprehensive evaluation and personalized management of pediatric ITP.